2017
DOI: 10.3390/ijerph14070696
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Transition and Biocultural Determinants of Obesity among Cameroonian Migrants in Urban Cameroon and France

Abstract: Native of rural West Cameroon, the Bamiléké population is traditionally predisposed to obesity. Bamiléké who migrated to urban areas additionally experience the nutrition transition. We investigated the biocultural determinants of obesity in Bamiléké who migrated to urban Cameroon (Yaoundé), or urban France (Paris). We conducted qualitative interviews (n = 36; 18 men) and a quantitative survey (n = 627; 266 men) of adults using two-stage sampling strategy, to determine the association of dietary intake, physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 71 publications
6
43
0
Order By: Relevance
“…A preliminary recent Senegalese study on body image also showed a female valorization of stoutness (Cohen et al, 2018), but further analyses have demonstrated that women particularly valued overweight and obesity in men while most participants overestimated their weighta trend probably linked to the traditional depreciation of thinness (Ndiaye, 2006). Hence, the binary logistic regression analysis showed the social valorization stoutness (overweight and obesity) to be an independent risk factor for overweight/obesity, as observed in previous studies conducted in Cameroon (Cohen et al, 2013(Cohen et al, , 2017, since the majority of overweight/obese subjects did not want to lose weighta phenomenon already identified in urban middle-aged Senegalese women (Holdsworth et al, 2004).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…A preliminary recent Senegalese study on body image also showed a female valorization of stoutness (Cohen et al, 2018), but further analyses have demonstrated that women particularly valued overweight and obesity in men while most participants overestimated their weighta trend probably linked to the traditional depreciation of thinness (Ndiaye, 2006). Hence, the binary logistic regression analysis showed the social valorization stoutness (overweight and obesity) to be an independent risk factor for overweight/obesity, as observed in previous studies conducted in Cameroon (Cohen et al, 2013(Cohen et al, , 2017, since the majority of overweight/obese subjects did not want to lose weighta phenomenon already identified in urban middle-aged Senegalese women (Holdsworth et al, 2004).…”
Section: Discussionsupporting
confidence: 73%
“…The Senegalese living in Dakar are exposed to both physical and social obesogenic pressures. Duration of urban residency has been shown to be a risk factor for overweight and obesity due to the adoption of urban obesogenic behaviours influenced by cultural values (Olszowy et al, 2015;Cohen et al, 2017). Indeed, urban Senegalese still value inappropriate overweight, ill-adapted to the urban ecosystem, and have adopted higher-calorie diets and abandoned regular physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed that the Senegalese tended to be more ectomorph, whilst Cameroonians tended to be more mesomorph. These results are in accordance with findings from recent studies conducted in Senegal and Cameroon [61,62], as Cameroonians have a higher BMI than Senegalese, which impacts on the somatotype frequency [63]. The BOSHAS is the first body image scale to rigorously and accurately capture a large variation in African body shape.…”
Section: Discussionsupporting
confidence: 90%